2007
DOI: 10.1073/pnas.0707570104
|View full text |Cite
|
Sign up to set email alerts
|

Skewed association of polyfunctional antigen-specific CD8 T cell populations with HLA-B genotype

Abstract: We studied CD8 T cell responses against HIV-1, cytomegalovirus, Epstein-Barr virus, and influenza in 128 subjects and demonstrate that polyfunctional CD8 T cell responses, also including IL-2 production and Ag-specific proliferation, are predominantly driven by virus epitopes restricted by HLA-B alleles. Interestingly, these protective CD8 T cells are equipped with low-avidity T cell receptors (TCRs) for the cognate virus epitope. Conversely, HLA-Arestricted epitopes are mostly associated with ''only effector'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
110
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 32 publications
(52 reference statements)
10
110
0
Order By: Relevance
“…This was particularly intriguing for the D b PA 224 -specific population, where we saw clear partitioning of clonotypes in the highavidity subset, and suggests that polyfunctionality (at least for this epitope) is not a selective characteristic of the high-avidity population. This is supported by one study (15) in which polyfunctionality correlated more closely with the HLA restriction element and was inversely correlated with avidity, but contrasts with a number of other studies (including our own) that have indicated a link between the strength of the TCR-pMHCI interaction and the propensity to produce multiple cytokines (6,7,13,14,19). Critically, however, the nexus between avidity and polyfunctionality in the majority of these studies was correlative, leaving open the possibility that these two effects segregate independently.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…This was particularly intriguing for the D b PA 224 -specific population, where we saw clear partitioning of clonotypes in the highavidity subset, and suggests that polyfunctionality (at least for this epitope) is not a selective characteristic of the high-avidity population. This is supported by one study (15) in which polyfunctionality correlated more closely with the HLA restriction element and was inversely correlated with avidity, but contrasts with a number of other studies (including our own) that have indicated a link between the strength of the TCR-pMHCI interaction and the propensity to produce multiple cytokines (6,7,13,14,19). Critically, however, the nexus between avidity and polyfunctionality in the majority of these studies was correlative, leaving open the possibility that these two effects segregate independently.…”
Section: Discussionmentioning
confidence: 49%
“…Although there have been several reports linking the functional profiles of T cell populations and their avidity or sensitivity to Ag (6,13,14), these analyses have been largely correlative. Furthermore, other evidence suggests that polyfunctional HIV-specific T cells partition preferentially with the set showing lower TCR avidity (15). Thus, the key determinants of polyfunctionality in virus-specific CD8 + T cells, particularly the role of T cell avidity, remain unclear.…”
Section: A Fter Virus Infection Cd8mentioning
confidence: 99%
“…All medium and supplements were purchased from Invitrogen (Carlsbad, CA). [18][19][20][21][22][23][24][25][26][27] were from ProImmune (Oxford, U.K.). For intracellular cytokine staining (ICS) multicolor FACS staining, TCR-transduced PBMCs were incubated overnight with indicated stimuli.…”
Section: Cell Linesmentioning
confidence: 99%
“…Notwithstanding the intrinsic superior antiviral activity of higher avidity TCR CD8 T cells, low-avidity TCR polyfunctional CD8 T cells have been suggested to be more fit in providing disease control during chronic virus infection (18) and have been reported to reject tumors and can have less problems regarding immune pathology (19). Although high-avidity CTLs are superior for viral and tumor clearance, they also have a greater sensitivity to Ag-induced cell death.…”
mentioning
confidence: 99%
See 1 more Smart Citation